Working conditions of nurses and the forms of contracting in Medellín, Colombia - Zapata Herrera, Marleny; Zapata Gómez, Nora Eugenia (Universidad y Salud, 2015)
Objective: To describe the conditions of work and organization of professional nursing in different forms of contracting. Materials and methods: A descriptive, cross-sectional study was made by selecting 552 nurses who were working in institutions of 2°, 3° and 4° health care level in a Colombian city; with a sample size for conglomerate represented by 31 IPS. The questionnaire on working conditions (qCT) validated for Latin America was used. Results: Nurses aged between 25 and 34 years (55%) prevailed, those who were single 52%, in private institutions 63.5% and with an indefinite-term contract 51%. The average assessment of the conditions of work and organization was positive in all scales qCT according to the mean and standard deviation. The type of hiring is important in the determination of working conditions, but it is not the only indicator. Conclusion: The best conditions of work and organization such as greater seniority, higher salary, total coverage of the social security and social benefits, are given to nurses who work in indefinite-term contract and private companies.